Urethral Catheterization for Urinary Retention in Women (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2021)
Introduction: Urinary retention is the inability to voluntarily pass urine with female:male ratio of 1:13. It may result from obstruction, infection, stenosis, etc. Urinary tract infection (UTI) causes inflammation and swelling of the urethra resulting in compression of the urethra and urinary retention. Objectives: Urinary retention in women is a rare occurrence and thus needs further evaluation. Case Presentation: 54 years old female were admitted to the ER with urinary retention and dull suprapubic pain, she had the history of diabetes and difficulty to urinate since 3 months ago. The bladder was quite distended. Insertion of 16-Fr foley catheter was attempted, and the output was around 20 ml of cloudy-yellowish fluid, with the second attempt of 24-Fr three-way foley catheter, around 1000ml of urine -suggestive of pyuria- was drained. Abdominal USG reported bilateral hydronephrosis, sludge debris in the bladder, and chronic cystitis. Discussion: The etiology of obstruction in this patient is cystitis that associates with diabetic bladder dysfunction. Risk factors for cystitis which we found in this patient are female, post menopause, old age, previous UTI, and diabetes. Diabetes may lead to diabetic bladder dysfunction with impaired detrusor contractility resulting in impaired bladder emptying and elevated residual urine. These conditions may result in chronic cystitis and the buildup of sludge debris on the bladder obstructing the hole of the urethral catheter. Thus, a larger size with a larger hole catheter that can evacuate the sludge debris is needed. Conclusion: In female patients with urinary retention and UTI and failure of urethral catheterization without resistance and contraindications, we recommend using larger size of urethral catheter before suprapubic catheter.